Uso dos conceitos de rua completa e integração modal na promoção e implantação de mobilidade sustentável em cidades de médio porte brasileiras - Silva, Michelle Trevisan da (2017)
Last decades, Brazilian’s old and new cities have significantly increasing due their population growing. However this growth occurred in a disorderly manner causing a decentralized model of occupation that together with economic, social and political factors, resulted in a non-sustainable model of mobility, due private vehicle travel became modal priority over other. The integration between public transport and active modal transport appears as an alternative to increase sustainable mobi lity rates in cities, making the system more efficient. By promoting flexibility of movement alternatives, it is allowed the individual to freely transit, this enables the user to decide which mode or combination of modes brings the greatest benefit to your path among available in order to improve the characteristics of the journey making it customized according to your needs. The aim of this research is determining the implementation guidelines and the simulation of the application of modal integration between public transport and active modal shift into Brazilian mid-sized town. In order to achieve this goal, an applied methodology divided into three stages was suggested: The best practices of sustainable mobility projects were grouped and deployment guidelines modal integration were listed. In a second stage, they were deployed in a simulation in the test area g enerating a georeferenced analysis model of the proposed system through the construction of thematic maps in ArcGIS software and sketches in StreetMix software. Finally, the system analysis and its implementation impacts were carried out through the evalua tion of it by indicators of sustainable urban mobility project and through focus groups of experts and local stakeholders. The results indicate that the diversity indixes in urban mobility of cities can be increased through the integrated transport system and it has wide acceptance in the evaluation of the specialists, helping to promote a new vision about the concepts of urban mobility, with focus in sustainable development.